Biting flies and trypanosomiasis in Sahom livestock farm: ‘The Missing Link’ - Premaalatha, B.; Tan, W. W.; Jamnah, O.; Zaini, C. M.; Erwanas, A.; Reuben, S. K. S.; Chandrawathani, P.; Ramlan, M. (Department of Veterinary Services Malaysia, 2016)
Trypanosomiasis positive cases were reported in Sahom Farm Retreat in Gopeng, Perak; with multispecies livestock animals. Nzi and Vavoua traps were applied to survey the population of biting flies; stable flies (Muscidae: Stomoxyinae) and horse flies (Tabanidae) as the vector for surra. Results indicated the presence of Trypanosomiasis infection diagnosed by buffy coat examination, thin blood stained smears and serological test (Surra Sero K-Set test) and identification of its insect vectors. The presence of both biting flies provides the missing link between the occurrence of the disease and host or environmental factors precipitating the disease. Besides trypanosomiasis in cattle, other parasitic infections were also recorded with heavy infections for liver fluke (Fasciola gigantica ova) and coccidia oocysts. Therefore, some control measures are recommended to eradicate the vectors and to treat infected animals in order to prevent the dissemination of the trypanosmiasis.